Inquiry Learning Model Assisted by Factile Application to Improve Science Learning Outcomes - Anisa Nurul Firdaus; Achmad Fathoni (Universitas Pendidikan Ganesha, 2023)
The low quality of education in Indonesia, particularly at the primary and secondary levels, is a major problem for the country's human resource capacity. Various efforts have been made to improve the quality of education nationally through several channels. Thus, this study aims to analyze the effect of the factile application-assisted inquiry learning model in improving students' science learning achievement. This research uses a quantitative approach with the type of quasi-experimental research. This study surveyed 78 participants in two classes, 38 and 40 respectively. Data was collected using the test method with an instrument in the form of a science learning achievement test. Data collection was carried out through pretest and posttest. The analysis showed that the average posttest score for the control class assisted by factile applications was 86.12, while the average pretest learning achievement for the experimental class was 86.96. The Kolmogorov-Smirnov normality test shows that the data follows a normal distribution. The t-test results showed an effect of factile application-assisted inquiry models on the science learning outcomes of grade IV students. It was concluded that the factile application-assisted inquiry learning model affected the learning outcomes of elementary school students.